Cultural competency among Lithuanian nurses and preparedness to work with intercultural immigrants: A quantitative study protocol - El Arab, Rabie Adel; Urbanavice, Rita; Jakavonyte-Akstiniene, Agne; Skvarcevskaja, Marija; Austys, Donatas; Mateos, Jose Tomas; Briones-Vozmediano, Erica; Rubinat-Arnaldo, Esther; Istomina, Natalja (Frontiers in Public Health, 2022)
Introduction Health care providers are increasingly required to provide care to patients from diverse cultural backgrounds. A culturally competent approach could be used to address gaps in the health care of migrants, whether they are refugees, asylum seekers, or undocumented migrants. From June 2021 onward, there are estimated to be 4,300 asylum seekers in Lithuania who crossed the Belarusian border. Furthermore, 65 thousand Ukrainians registered within 6 months of the beginning of the war on 24 February 2022. Aim To determine the cultural competence of Lithuanian nurses using the Nurse Cultural Competence Scale (NCCS) questionnaire. Methods A quantitative study evaluating the cultural competency of nursing professionals will be conducted using the Lithuanian version of the Nurse Cultural Competence Scale (NCCS). The study will be conducted in Lithuanian municipalities and will involve primary, secondary, and tertiary health care providers. Discussion This study will provide data that can guide the development and evaluation of interventions designed to reduce health disparities among migrants, including the need to identify the appropriate type of cultural competency training for nurses. In addition to the results of this study, it may provide an indication of other cultural competency required for nurses. This includes consideration of religion, sexual orientation, gender identity, household classifications on the basis of urban vs. rural areas, language spoken, and country of origin.